Analisis Deskriptif Profil Kemiskinan Indonesia Berdasarkan Data BPS Tahun 2023 - Purwanti, Endang (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Poverty remains a serious issue haunting Indonesia, affecting the lives of millions of its inhabitants. To comprehend the dynamics of poverty, a thorough analysis of Indonesia's poverty profile from 2019 to 2023 is necessary. This is crucial for laying the foundation for the formulation of more effective policies to address the challenges of poverty in the future. The research aims to provide a comprehensive overview of Indonesia's poverty profile during the specified period, utilizing a descriptive analysis approach with secondary data from various official sources, including the Central Statistics Agency (BPS). Data analysis employs descriptive statistical methods to depict the distribution of poverty in Indonesia from 2019 to 2023. The findings indicate that during this period, both the total number and percentage of the population living in poverty experienced a decline. Nevertheless, poverty remains more concentrated in rural areas. The impoverished population tends to be dominated by individuals with low educational attainment, younger age groups, and those engaged in informal employment.